(untitled) (Research, Society and Development, 2020)
Pseudocereal mucilages have applications in the bakery industry as a thickener, gelling and emulsifier. This study aimed at the demonstration of the influence of the addition of mucilages of chia seeds (Salvia hispanica L.) and brown flaxseeds (Linum usitatissimum L) on the technological quality of breads. Physico-chemical analyses of mucilages and wheat flour were performed (wet gluten and wheat flour index) and the physical and technological characteristics of the bread. The evaluation of the bread’s texture parameters twas made through the central rotational composite design, by response surface methodology and their respective contour curves. The mucilages of chia and flaxseed showed a humidity of 4.37% and 7.23%; ashes 7.56% and 4.42%; proteins 16.32% and 17.69%; 2.79% lipids 0.98%; and carbohydrates 21.43% and 23.47% respectively. The increase in the concentrations of flaxseed (> 0.3%) and chia (0.1 to 0.4%) mucilages, led to an increase in breads’ hardness. However, this effect was not observed in elasticity and cohesion. The luminosity of the crumb varied according to the concentration of the added mucilages, approaching the black colour and showing that the colour of the mucilages significantly influenced the colour of the bread crumb. Considering the results obtained, the addition of mucilages positively affected the quality characteristics of the bread.